2007
DOI: 10.1016/j.brainres.2007.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent effect of epidural steroid on pain behavior induced by chronic compression of dorsal root ganglion in rats

Abstract: Although epidural steroid injection has been commonly used to treat radicular pain, its clinical efficacy remains controversial. In a rat model of radicular pain induced by chronic compression of lumbar dorsal root ganglion (CCD), we examined the effect of epidural steroid on CCD-induced pain behavior. Triamcinolone [a glucocorticoid receptor (GR) agonist] or RU38486 (a GR antagonist) was given epidurally once either on day 3 (early treatment) or day 10 (late treatment) after CCD. The results showed that 1) ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
(41 reference statements)
3
10
0
Order By: Relevance
“…Common to all the neuropathic pain models is a decrease in withdrawal threshold to mechanical or thermal stimulation, which is enhanced after exposure to stress. Studies using GR antagonists, such as mifepristone (MIFE), demonstrated that intrathecal administration could increase both mechanical and thermal withdrawal thresholds in the injured limb (Wang et al, 2004;Takasaki et al, 2005;Gu et al, 2007). Those results were also replicated with intrathecal administration of antisense oligodeoxynucleotides selective for GR (Wang et al, 2004;Dina et al, 2008).…”
Section: Receptors In Stress Pathways That Modulate Nociceptionsupporting
confidence: 63%
See 1 more Smart Citation
“…Common to all the neuropathic pain models is a decrease in withdrawal threshold to mechanical or thermal stimulation, which is enhanced after exposure to stress. Studies using GR antagonists, such as mifepristone (MIFE), demonstrated that intrathecal administration could increase both mechanical and thermal withdrawal thresholds in the injured limb (Wang et al, 2004;Takasaki et al, 2005;Gu et al, 2007). Those results were also replicated with intrathecal administration of antisense oligodeoxynucleotides selective for GR (Wang et al, 2004;Dina et al, 2008).…”
Section: Receptors In Stress Pathways That Modulate Nociceptionsupporting
confidence: 63%
“…Those results were also replicated with intrathecal administration of antisense oligodeoxynucleotides selective for GR (Wang et al, 2004;Dina et al, 2008). Conversely, administration of a GR agonist, dexamethasone or triamcinolone, mimicked stress-induced exacerbation of withdrawal threshold (Wang et al, 2004;Gu et al, 2007). Similarly, intrathecal dosing of an MR antagonist, spironolactone (SPIRO) or eplerenone, also reversed the allodynic responses (Gu et al, 2011;Dong et al, 2012).…”
Section: Receptors In Stress Pathways That Modulate Nociceptionsupporting
confidence: 53%
“…There are few preclinical studies directly examining behavioral effects of glucocorticoids delivered in or near the DRG, perhaps due to the difficulty in gaining access to the DRG in mice or rats. In two rat studies using a CCD model, the clinically used glucocorticoid triamcinolone applied epidurally reduced pain behaviors when given 3 days after the compression began [10,49]. However, different results were obtained when applying drugs at day 10; at this later time point, triamcinolone failed to improve pain behaviors while a glucocorticoid antagonist improved them [49].…”
Section: Reviewmentioning
confidence: 99%
“…Some of this effect may be due to direct effects on neurons, because eplerenone applied to small diameter cultured neurons in vitro could reverse some of the excitatory changes induced by DRG inflammation (Figure 3). In light of the study by Gu et al in which GR agonists had opposite effects at later time points [49], it will be important to determine if MR antagonists still have anti-nociceptive effects at later time points. In a study using an NP model, infiltration of the nerve root with the GR agonist dexamethasone at the time of NP application could block development of mechanical pain behaviors.…”
Section: Reviewmentioning
confidence: 99%
“…Amongst those, chronic compression of the dorsal root ganglion (CCD) model in rodents displayed dramatic pain hypersensitivity such as mechanical hypersensitivity (hyperalgesia and allodynia) and thermal hyperalgesia that mimic the pain symptom observed in low back pain patients [ 1 6 ]. Although epidural steroid injection and surgical intervention have been used both clinically and experimentally in many cases, radicular low back pain remains a common chronic pain condition that is sometimes refractory to current treatment modalities [ 7 , 8 ]. Therefore, development of new therapeutics is helpful and in urgent need towards the treatment of radicular low back pain.…”
Section: Introductionmentioning
confidence: 99%